The wisdom of distrust: reflections on Ukrainian society and sociology - Мельніков, Андрій Сергійович; Мельніков, А. С.; Мельников, Андрей Сергеевич; Melnikov, Andrii S.; Melnikov, A.; Melnikov, Andrew; Johnson, John M. (Bingley : Emerald Group Publishing Limited, 2009)
Ukraine regained its independence in 1991, following over 7 decades of soviet domination, and about 300 years of Russian domination. Democracy and stable institutional development have proven problematic for Ukraine since 1991, arguably more so than any of the other Eastern European countries. Unlike the increasing economic development in the other countries, for example, per capita GNP in Ukraine has decreased by approximately 50% in the last decade. President Viktor Yushchenko's “Orange Revolution” has promised certain westernized economic reforms, but political opposition has forced a new election scheduled for September 30, 2007.

Україна відновила свою незалежність у 1991 році після 7 років десятиліття радянського панування та близько 300 років російського панування. Демократія та стабільний інституційний розвиток виявились проблематичними для України з 1991 року, можливо, більше, ніж для будь-якої іншої країни Східної Європи. На відміну від зростаючого економічного розвитку в інших країнах, наприклад, ВНП на душу населення в Україні зменшився приблизно на 50% за останнє десятиліття. "Помаранчева революція" президента Віктора Ющенка обіцяла певні вестернізовані економічні реформи, але політична опозиція змусила провести нові вибори, призначені на 30 вересня 2007 року.

Украина восстановила свою независимость в 1991 году после более чем 7 десятилетий советского господства и около 300 лет российского господства. Демократия и стабильное институциональное развитие оказались проблематичными для Украины с 1991 года, возможно, больше, чем для любой другой страны Восточной Европы. В отличие от ускоряющегося экономического развития в других странах, например, ВНП на душу населения в Украине снизился примерно на 50% за последнее десятилетие. «Оранжевая революция» президента Виктора Ющенко обещала определенные прозападные экономические реформы, но политическая оппозиция вынудила провести новые выборы, намеченные на 30 сентября 2007 года.
Johnson J.M. The wisdom of distrust: reflections on Ukrainian society and sociology / J.M. Johnson, A. Melnikov // Denzin, N.K. (Ed.). - Studies in Symbolic Interaction. - Vol. 33. - Emerald Group Publishing Limited. - Bingley, 2009. - pp. 9-18.
Keywords: Ukrainian society; Russian domination; Democracy; “Orange Revolution”; українське суспільство; російське панування; демократія; “Помаранчева революція”; украинское общество; российское господство; демократия; "Оранжевая революция"; Research Subject Categories::SOCIAL SCIENCES